Labor Market Integration between Northern Mexico and Southern United States: an empirical investigation - Walter Cortez, Willy; Islas Camargo, Alejandro (Universidad Autónoma de Nuevo León, 2009)
In this paper, the analysis of co-dependence between the US and Mexico labor markets is carried out by estimating the cyclical component of California’s and Texas’ manufacturing employment and four US Border Mexican cities through the Hodrick-Prescott filter. We estimated the smoothing parameter following a calibration technique proposed by Guerrero et al (2001) which allows us to obtain the best linear unbiased estimator of the trend component. Our analysis suggests that after 1994 there has been greater labor market integration between Mexico’s northern region and US’ southern region. This greater integration has implied a change in the nature of the short term relationship of manufacturing employment between Mexico and the US. The change is also significant on the relationship between Mexican real wages and US employment.